2020
DOI: 10.1332/251510819x15728693158427
|View full text |Cite
|
Sign up to set email alerts
|

Urgency and ambition: the influence of political environment and emotion in spurring US women’s candidacies in 2018

Abstract: This article analyses publicly reported statements of motivation by non-incumbent women US House candidates in 2018 to assess the role of negative emotions, particularly those cued by catalysing events like the 2016 presidential election, in women candidate emergence. Findings reveal that Democratic non-incumbent women candidates were most likely to describe negative inducements, including feelings of urgency, anger and/or threat, as motivating candidacy, with these emotions slightly more evident in white wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…We provide a novel approach to understanding one aspect of the candidate emergence gap between men and women—motive—by examining differences in articulated interest underlying nascent ambition, and consider whether interest is expressed in communal or agentic terms. Although men and women express different motivations for running (Carroll and Sanbonmatsu 2013; Deckman 2004), and white women and non-white women express some motivational differences, as well (Dittmar 2020; Frederick 2013, 2014), we expect that regardless of sex or race and ethnicity, the invocation of agentic language will be more common among individuals who end up launching a campaign than individuals who do not end up launching a campaign.…”
Section: Political Ambition and Candidate Emergencementioning
confidence: 97%
See 2 more Smart Citations
“…We provide a novel approach to understanding one aspect of the candidate emergence gap between men and women—motive—by examining differences in articulated interest underlying nascent ambition, and consider whether interest is expressed in communal or agentic terms. Although men and women express different motivations for running (Carroll and Sanbonmatsu 2013; Deckman 2004), and white women and non-white women express some motivational differences, as well (Dittmar 2020; Frederick 2013, 2014), we expect that regardless of sex or race and ethnicity, the invocation of agentic language will be more common among individuals who end up launching a campaign than individuals who do not end up launching a campaign.…”
Section: Political Ambition and Candidate Emergencementioning
confidence: 97%
“…As Frederick (2013, 113) notes, “the growing literature on women’s paths to public office has not adequately grappled with the complexities that shape women’s ‘deciding to run’ accounts.” In this article, we use a supervised text analytic approach to examine whether accounts reflect gendered social roles and whether differences in these accounts are associated with emergence. Our analysis also takes into account whether the invocation of gendered social roles differs for white and non-white women, 1 building on scholarship that reveals intersectional dynamics in candidate emergence among women (Brown 2014; Dittmar 2020; Holman and Schneider 2018; Shah, Scott, and Juenke 2019; Shames et al 2020; Silva and Skulley 2018; Swain and Lien 2017). Just as gender norms inform how men and women articulate their interest in running for office, racialized standards may contribute to variations in articulated interest within the agency and communion framework for white and non-white men and women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dittmar (2020) finds that almost half of all Democratic nonincumbent female House candidates expressed urgency, anger, frustration, or threat in explaining why they ran for office in 2018. Just one in five GOP women described any of these feelings as motivating their candidacies.…”
mentioning
confidence: 99%
“…Some authors associate it with the newly instituted reservation of 30% of public campaign finance for women (Haje 2019). Meanwhile, others have observed that, as in the United States, the electoral popularity (and subsequent election) of a far-right and misogynist candidate, Jair Bolsonaro, might have increased women's costs of not running (Dittmar 2020). Within this context, and considering that many politicians start their careers at the local level, the 2020 elections were expected to be a turning point for women's political participation in Brazil.…”
mentioning
confidence: 99%